2009
DOI: 10.1017/s0031182009006039
|View full text |Cite
|
Sign up to set email alerts
|

Helminth species richness in wild wood mice,Apodemus sylvaticus, is enhanced by the presence of the intestinal nematodeHeligmosomoides polygyrus

Abstract: We analysed 3 independently collected datasets of fully censused helminth burdens in wood mice, Apodemus sylvaticus, testing the a priori hypothesis of Behnke et al. (2005) that the presence of the intestinal nematode Heligmosomoides polygyrus predisposes wood mice to carrying other species of helminths. In Portugal, mice carrying H. polygyrus showed a higher prevalence of other helminths but the magnitude of the effect was seasonal. In Egham, mice with H. polygyrus showed a higher prevalence of other helminth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 45 publications
2
41
1
Order By: Relevance
“…In their natural hosts, heligmosomoid nematodes can show a pronounced pattern of co-infection with other parasite species [4], [57], [58]. We did not observe any co-occurrence effects of studied parasite species, rather the opposite.…”
Section: Discussioncontrasting
confidence: 54%
“…In their natural hosts, heligmosomoid nematodes can show a pronounced pattern of co-infection with other parasite species [4], [57], [58]. We did not observe any co-occurrence effects of studied parasite species, rather the opposite.…”
Section: Discussioncontrasting
confidence: 54%
“…Behnke et al (2009) concluded that H. polygyrus has an effect on other co-infecting helminths in wood mice, and therefore that quantitative interactions between helminths infecting wild wood mice exist and contribute to the infracommunity structure at individual host level, and to the component community structure at population level. Thus, this nematode might play an important role in helminth community stability, explaining the high prevalence of infection detected.…”
Section: Discussionmentioning
confidence: 99%
“…Also, pairs of significantly associated species consisted, in 3 of the 4 cases, of species living in different microhabitats within the host, suggesting that immune-mediated effects are more likely explanations than active resource competition. Recent studies have emphasized that positive interactions are as frequent, if not more frequent, than negative ones in helminth communities of rodents and other mammals (Behnke et al 2005(Behnke et al , 2009Lello et al 2004). For instance, Behnke et al (2009) have provided data suggesting that the nematode Heligmosomoides polygyrus facilitates infection of its rodent host, Apodemus sylvaticus, by other helminths by suppressing parts of its immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have emphasized that positive interactions are as frequent, if not more frequent, than negative ones in helminth communities of rodents and other mammals (Behnke et al 2005(Behnke et al , 2009Lello et al 2004). For instance, Behnke et al (2009) have provided data suggesting that the nematode Heligmosomoides polygyrus facilitates infection of its rodent host, Apodemus sylvaticus, by other helminths by suppressing parts of its immune response. In our study, 3 of 4 significant associations were positive, suggesting either some form of facilitation as in the preceding example, or that both species are acquired together in a way that generates a statistical association.…”
Section: Discussionmentioning
confidence: 99%